2020
DOI: 10.1021/acs.langmuir.9b03475
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a New Method to Study the Effects of Surface Functional Groups on Adsorption of CO2 and CH4 on Activated Carbons

Abstract: The commercial coconut shell-activated carbon was modified to change the number of oxygen-containing functional groups. N2 adsorption/desorption isotherms, Fourier transform infrared (FT-IR), and Boehm titration were adopted to describe the physical and chemical properties of the samples. The adsorption isotherms of CO2 and CH4 on both the unmodified and modified samples were measured. To better understand the effects of surface oxygen-containing functional groups on adsorption of CO2 and CH4, the overall adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…Meanwhile, that of methane on 55‐KAC decreases by 0.17 mmol g −1 . This result proves that the adsorption capacity of carbon dioxide is influenced by both pore structure and surface chemical properties again [15, 33].…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Meanwhile, that of methane on 55‐KAC decreases by 0.17 mmol g −1 . This result proves that the adsorption capacity of carbon dioxide is influenced by both pore structure and surface chemical properties again [15, 33].…”
Section: Resultssupporting
confidence: 59%
“…Meanwhile, that of methane on 55-KAC decreases by 0.17 mmol g À 1 . This result proves that the adsorption capacity of carbon dioxide is influenced by both pore structure and surface chemical properties again [15,33]. The separation of carbon dioxide/methane mixture on the modified samples also raises with the increasing modification temperature, Figure 4.…”
Section: Effects Of Modification Temperature On Adsorption and Separa...supporting
confidence: 52%
See 1 more Smart Citation
“…The difference between the images captured by mobile and the images captured by standard tongue diagnostic devices lies in noise and picture resolution, and the images captured by mobile in the tongue image processing method require algorithms to exclude the influence of light and background. Song et al 11 applied the algorithm of LBP (Local Binary Patterns) combined with Adaboost in a cell phone terminal to achieve near real-time tongue image detection, and the accuracy of image analysis was achieved by deep learning algorithm through a residual network without setting the scene. In order to construct a color correction function model for tongue images based on cell phone terminals, Wang et al 12 compared tongue images taken by different models of cell phones with those taken by the TDA-1 micro-tongue diagnostic instrument, and analyzed more than 300 cases of tongue images for standard color card L*a*b color value acquisition; with the optimized back propagation (BP) neural network as the model, the constructed network can correct tongue color and moss color.…”
Section: Related Workmentioning
confidence: 99%
“…It also has been suggested that the surface chemistry, rather than the textural properties, governs the CO 2 capture performance at lower pressures, while the textural properties become more important at higher CO 2 pressures, when the adsorption process becomes controlled by the micropore filling mechanism [41,42]. Carboxyls and hydroxyls have been suggested as the most effective oxygenated functionalities for selective adsorption of CO 2 , due to their high polarity, compared to carbonyls and ethers [43,44]. A recent work reported that oxygen can actually be detrimental to the capture performance, although in this case the focus was on the external surface functionalisation [45].…”
Section: Introductionmentioning
confidence: 99%